Avaliação da influência do transporte eólico na evolução da desembocadura do estuário do Rio Coreaú, Camocim - CE - Camelo, Carlos Eduardo Castro Jorge (2013)
Estuary from semiarid tropical áreas are subject to strong morphdynamics processes. Therefore they configuration is modified at different spatial and temporal scales. The factors that act into between that process can be natural or anthropogenic. In relation to natural process is particular importance of Intertropical Convergence Zone (ITCZ) wich operates in seasonality rainy season, wind and changes sediment transport. The point of this work is to assess the influence of aeolian transport in evolution of estuary outfall Coreaú river. For this pourpose, fields campaing, in october 2012, and march 2013 were performed. Ten Leatherman sand traps were installed along for each transect on the dune and spit in a range of eight consecutive hours, with opening facing windward for the two features for to collect sediments, and subsequent size analyzes, calculation of volume and transport rate. In the right bank of estuary was carried out traversal shoreline in those months bypassing the spit up at the dune at high tide spring tide. Speed and wind direction was measured with anemometer. The correlations of rates sediment transported by wind speed leads to the conclusion that the influence of aeolian sediment transport in estuary mouth Coreaú river is more significant in the dry season considering the wind speed is most intense in this period, with a greater contribution dune with fine-grain size than sediments spits with coarse grain size. From the association of main winds direction with the traverse of the shoreline is possible to note that there is a migration of dune and spit towards estuary.